Democratização da Filosofia no Brasil: um blog sobre filosofia e a leitura de Byung-Chul Han - Corrêa, Vinicius Martins (Universidade Federal do Tocantins, 2023)
The theoretical proposal of the present work, about the democratization of philosophy, is based on the exposition of the "product" blog "Chaves and Philosophy", created to help in the teaching of the subject in high school classes. Besides the issue of democratization, a problematization about the popularization process of philosophy was developed. Beyond this popularization, we tried to think about the criticism of the technique (internet), which in the current context can help popularize philosophy, without, however, completing the process towards democratization. The mere transfer of philosophical content to the Internet, as already said, can popularize philosophy, reaching more and more people, but it does not bring in itself a greater opening that would be given in the democratization process. The thinker Byung-Chul Han helps us to reflect on this process, especially on the relations of biopower, psychopolitics, and on the new mediations that the internet subjects us to. Despite this current reflection, the democratization of philosophy in Brazil cannot be discussed without a background Brazilian context. At this point, there is a more panoramic approach on Philosophy in Brazil. Therefore, we have an exercise of the past, to contextualize Philosophy in Brazil, of the present, reflecting on the popularization and its contradictions, and finally, of the future, to think about philosophy within a focus that thinks about the democratization of philosophy in Brazil as an essential part of change for the future of the teaching of this discipline in the country, extremely threatened at the present time.